Hemodynamics of Prefrontal Cortex in Ornithine Transcarbamylase Deficiency: A Twin Case Study - Anderson, Afrouz A.; Gropman, Andrea; Le Mons, Cynthia; Stratakis, Constantine A.; Gandjbakhche, Amir H. (Frontiers in Neurology, 2020)
Ornithine transcarbamylase deficiency (OTCD) is the most common form of urea cycle disorder characterized by presence of hyperammonia (HA). In patients with OTCD, HA is known to cause impairments in domains of executive function and working memory. Monitoring OTCD progression and investigating neurocognitive biomarkers can therefore become critical in understanding the underlying brain function in population with OTCD. We used functional Near Infrared Spectroscopy (fNIRS) to examine the hemodynamics of prefrontal cortex (PFC) in a fraternal twin with and without OTCD. fNIRS is a non-invasive and wearable optical technology that can be used to assess cortical hemodynamics in realistic clinical setting. We quantified the hemodynamic variations in total-hemoglobin, as assessed by fNIRS, while subjects performed the N-Back Working Memory (WM) task. Our preliminary results showed that the sibling with OTCD had higher variation in a very low frequency band (<0.03 Hz, related to mechanism of cerebral autoregulation) compared to the control sibling. The difference between these variations were not as prominent in the higher frequency band, indicating the possible role of impaired autoregulation and cognitive function due to presence of HA. We further examined the functional connectivity in PFC, where the OTCD sibling showed lower interhemispheric functional connectivity as the task load increased. Our pilot results are the first to show the utility of fNIRS in monitoring OTCD cortical hemodynamics, indicating the possibility of inefficient neurocognitive function. This study provides a novel insight into the monitoring of OTCD focusing on the contribution of physiological process and neurocognitive function in this population.